Glioma-targeted gamma-polyglutamic acid / chitosan core-shell nanoparticles and preparation method thereof

By designing γ-polyglutamic acid/chitosan core-shell nanoparticles, using the targeted delivery mechanism of Cu-Cur and lactoferrin, combined with the pH/redox reaction of the tumor microenvironment, high efficiency in brain glioma is achieved Drug release and apoptosis effects solve the problems of targeted delivery and low drug transmission efficiency in brain glioma treatment, and significantly improve the therapeutic effect.

CN119236103APending Publication Date: 2025-01-03CHINA PHARM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411364349.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The treatment of brain glioma is facing the problem of difficult time to cross the blood-brain barrier in the targeted delivery system, low drug transmission efficiency and complexity of the tumor microenvironment, resulting in the problems of large side effects and poor efficacy of existing treatment methods.

Method used

A γ-polyglutamic acid/chitosan core-shell nanoparticles were designed to form Cu-Cur nanoparticles through coordination drive, combining lactoferrin and sialic acid receptors, and using a pH/redox dual response mechanism Release of curcumin and copper ions in tumor cells, induce Fenton-like reactions, and achieve targeted delivery and apoptosis effects.

Benefits of technology

It has achieved efficient enrichment of nanoparticles and rapid release of drugs in brain gliomas, significantly improving the anti-tumor efficacy, which is more significant than a single method, and the raw materials are non-toxic and have high biocompatible.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236103A_ABST
    Figure CN119236103A_ABST
Patent Text Reader

Abstract

The invention discloses a brain glioma targeted gamma-polyglutamic acid / chitosan core-shell nanoparticle, which is characterized in that the gamma-polyglutamic acid / chitosan core-shell nanoparticle takes a cation nanoparticle as an inner core, and the cation nanoparticle is formed by caffeic acid grafted chitosan-copper-curcumin through coordination driving self-assembly; phenylboronic acid modified gamma-polyglutamic acid is used as an anion shell, and gamma-polyglutamic acid / chitosan core-shell nanoparticles are formed through electrostatic interaction and mutual combination of pH-sensitive boric acid ester bonds. Then, lactoferrin is further modified on the surface of the nanoparticle through electrostatic adsorption, and the glioma targeted gamma-polyglutamic acid / chitosan core-shell nanoparticle is constructed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of pharmaceutical preparations, and in particular relates to a glioma-targeted gamma-polyglutamic acid / chitosan core-shell nanoparticle and a preparation method thereof. Background Art

[0002] Glioblastoma (GBM) refers to a primary brain tumor caused by cancerous changes in glial cells in the brain and spinal cord. In my country, the annual incidence of glioma is as high as 5-8 people per 100,000 people. At present, surgery combined with radiotherapy and chemotherapy is the current standard of treatment for newly diagnosed GBM patients. However, due to the strong invasiveness of gliomas and unclear tumor boundaries, tumor cells are difficult to be completely eliminated during surgery, which can easily lead to recurrence. At the same time, chemotherapy and radiotherapy have large side effects, which can affect the patient's daily life in severe cases. In addition, due to the poor permeability of most chemotherapy drugs, it is difficult to penetrate the blood-brain barrier (BBB) ​​and accumulate in the brain. Therefore, designing a safe and effective targeted delivery system across the BBB is the focus of current research on the treatment of GBM.

[0003] Curcumin (Cur), a rhizome extract of turmeric, a ginger plant, has a wide range of pharmacological effects, including anti-inflammatory, antioxidant, and anti-tumor effects. Clinical studies have shown that Cur, alone or in combination with other drugs, has a good anti-cancer effect on cancer patients with almost no adverse reactions. Cur's anti-cancer effect is multi-targeted, and it can regulate almost all types of cancer states, including cell proliferation, cancer signaling pathways, transcription factors, and tumor angiogenesis. Studies have shown that Cur can be used as a potential anticancer agent for the treatment of glioblastoma through the following molecular mechanisms, including inhibiting the proliferation of glioblastoma cells, inducing G2 / M phase arrest and apoptosis, and increasing the expression level of death-associated protein kinase 1 in glioblastoma cells, thereby exerting an anti-cancer effect.

[0004] Due to the complexity of the tumor microenvironment, a single treatment strategy is difficult to effectively eliminate the tumor, so multiple methods are needed to overcome the shortcomings of a single treatment strategy. Chemodynamic therapy (CDT) is a promising cancer treatment model that utilizes endogenously overexpressed hydrogen peroxide (H2O2) in tumors to produce toxic hydroxyl radicals (·OH) through metal ion-catalyzed Fenton / Fenton-like reactions, thereby inducing apoptosis or necrosis of tumor cells. Combining anticancer drugs with CDT-active nanomaterials is expected to achieve synergistically enhanced antitumor effects. 2+ Compared with Cu-mediated CDT, + The Fenton-like reaction catalyzed by Fe is more favorable both kinetically and energetically, and its catalytic activity is higher than that of Fe 2+ When the nanoparticles are taken up by cancer cells, the metal ions will undergo a redox reaction with glutathione (GSH) and H2O2 overexpressed in the tumor cells. First, GSH will convert Cu2+ Reduction to Cu + , and oxidized GSH (GSSG) is generated. Then, Cu + It reacts with H2O2 to generate ·OH, which causes apoptosis of tumor cells.

[0005] Core-shell nanoparticles with charge reversal show unique advantages in improving targeted delivery efficiency. Although negatively charged nanoparticles can prolong their circulation time in the blood, they are not easily taken up by tumor cells due to the negative charge of their surface, resulting in reduced drug delivery efficiency. Positively charged nanoparticles show high cellular uptake due to enhanced interaction with tumor cells, but are easily cleared by the endothelial reticular system. Therefore, a charge reversal strategy is introduced to achieve a long circulation effect in the body by constructing a negatively charged shell to shield the positively charged nanoparticle core. At the same time, under specific stimulation of the tumor microenvironment (including pH, enzymes and other factors), the negatively charged shell can be disintegrated, and the subsequently exposed positively charged nanoparticle core is more easily taken up by tumor cells.

[0006] Gliomas have a complex BBB system, and the subsequent EPR effect is much weaker than that of peripheral tumors. It is insufficient to treat GBM by relying solely on passive targeting based on the EPR effect. The introduction of ligand targeting strategies can help improve the therapeutic effect of GBM. Compared with single ligands, dual ligand targeting has better selectivity. Compared with normal tissue cells, low-density lipoprotein receptor-related protein 1 is highly expressed on the surface of BBB endothelial cells and tumor cells, and sialic acid receptors are also overexpressed in tumor cells. Dual-targeted ligand-modified nanoparticles can be designed for these two receptors, which provides more possibilities for increasing the penetration of drugs through the BBB to reach tumor cells and improving the therapeutic effect of GBM. Summary of the invention

[0007] Based on the above prior art, the present invention provides a glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticle And its preparation method. The present invention is Grafting Caffeic acid (CA) of Chitosan (CS) The framework (CC) is selected, the amino group in CS and the catechol structure in CA are selected as high affinity anchor points for nanoparticle coordination, and divalent copper (Cu(II)) is used as a coordination bridge and intermediate. Curcumin (Cur) A glutathione (GSH)-responsive drug delivery system (CC-Cu-CurNPs) based on coordination-driven self-assembly was prepared by using the diketo / enol part with coordination binding ability; Phenylboronic acid (PBA) Grafted γ- Polyglutamic acid (γ-PGA)(PP) is the shell to shield the positive charge of CC-Cu-CurNPs. The positively charged core CC-Cu-CurNPs and the negatively charged shell PP are combined with each other through electrostatic interaction and pH-sensitive borate bonds to form γ-polyglutamic acid / chitosan core-shell nanoparticles (PP / CC-Cu-Cur NPs). Finally, electrostatic interaction is used to adsorb positively charged Lf on the surface of the nanoparticles to construct a glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticle (Lf-PP / CC-Cu-CurNPs). The nanoparticles can further target gliomas through the BBB and have pH / redox dual response capabilities. After Lf-PP / CC-Cu-.Cur NPs are administered intravenously and enter the blood circulation, they are Lactoferrin (Lf) The targeted effect of Lf-PP / CC-Cu-Cur NPs is enriched in the brain through the BBB; PBA can further bind to the sialic acid (SA) receptors overexpressed on the surface of tumor cells, and Lf can also bind to the low-density lipoprotein receptor-related protein 1 on the surface of tumor cells, so that Lf-PP / CC-Cu-Cur NPs are enriched in brain gliomas: the pH-responsive boronate bond breaks after reaching the tumor microenvironment (pH 6.5), and the anionic shell layer PP is removed, exposing the positively charged core CC-Cu-CurNPs, which is easier to be taken up by tumor cells; the high concentration of GSH in tumor cells competes for the coordination sites between Cu, CA and Cur, accelerating the disintegration of the positively charged core, so that Cur and Cu 2+ Rapid release; on the one hand, the released natural compound Cur directly exerts anti-tumor efficacy; on the other hand, the copper ion-mediated Fenton-like reaction produces toxic ·OH, which can induce apoptosis of tumor cells.

[0008] The invention successfully prepares a kind of glioma-targeted gamma-polyglutamic acid / chitosan core-shell nanoparticles, and the prepared nanoparticles are evenly dispersed and have uniform particle size.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] The invention discloses a glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticle, which is characterized in that the γ-polyglutamic acid / chitosan core-shell nanoparticle is a cationic nanoparticle formed by self-assembly driven by caffeic acid (CA) grafted chitosan (CS)-copper-curcumin (Cur) coordination as the core, and phenylboronic acid (PBA) modified γ-polyglutamic acid (γ-PGA) as the anionic shell, which is mutually combined through electrostatic action and pH-sensitive borate bonds to form γ-polyglutamic acid / chitosan core-shell nanoparticles; then, lactoferrin (Lf) is further modified on the surface of the nanoparticle by electrostatic adsorption, so as to construct a glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticle.

[0011] Furthermore, the method for preparing the glioma-targeted γ-polyglutamic acid-chitosan core-shell nanoparticles of the present invention comprises the following specific steps:

[0012] (1) Weigh 100 mg of CS, dissolve it in 10 mL of acetic acid (1%, v / v), and dilute it with an appropriate amount of methanol while stirring at room temperature. Take 51 mg of CA and dissolve it in an appropriate amount of methanol, and add it to the CS solution; then continue to add catalyst EDC (81.2 mg) and NHS (48.8 mg) to react with the amino group in CS to form an amide bond; the resulting reaction mixture is stirred at room temperature for 24 hours, dialyzed with an excess of water / methanol mixture (1:4, v / v) for 2 days, filtered through a 0.8 μm microporous filter membrane, and then freeze-dried to obtain a light brown CC powder for use;

[0013] (2) Weigh 17.64 mg of γ-PGA and dissolve it in an appropriate amount of DMSO:H2O (1:1, v / v). After dissolution, add catalyst EDC (46 mg) and NHS (27.6 mg) and activate in an ice bath for 1 h. Then slowly add a small amount of triethylamine dropwise while stirring until the pH of the final solution is adjusted to be weakly alkaline. Weigh 22.3 mg of PBA and dissolve it in an appropriate amount of DMSO:H2O (1:1, v / v). After complete dissolution, add it dropwise to the above y-PGA solution, react at room temperature for 24 h, dialyze in pure water for 2 days, filter through a 0.8 μm microporous filter membrane, and then freeze-dry to obtain a white sponge-like PP solid for use.

[0014] (3) Under magnetic stirring, 8.5 mL CC (pH 6.5, 1 mg / mL), 0.5 mL CuCl2 (10 mM), and 1 mL Cur (2 mg / mL) were mixed and reacted at room temperature for 15 min. Subsequently, the reaction solution was rotary evaporated at 40 °C to remove ethanol and filtered through a 0.8 μm microporous filter to obtain CC-Cu-Cur NPs.

[0015] (4) Under magnetic stirring, 1 mL of CC-Cu-Cur NPs was dropped into 3 mL of 10 mg / mL PP deionized water solution and stirred for 3 h at room temperature to obtain PP / CC-Cu-Cur NPs;

[0016] (5) Under magnetic stirring, 1 ml of 3 mg / mL Lf was added dropwise to 5 mL of PP / CC-Cu-Cur NPs system and reacted at room temperature for 12 h to obtain Lf-PP / CC-Cu-Cur NPs.

[0017] The present invention provides an application of glioma-targeted gamma-polyglutamic acid / chitosan core-shell nanoparticles in the preparation of glioma products.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention provides a method for preparing glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticles, which are of suitable size and uniform particle size, can penetrate the BBB through the targeting action of Lf and PBA, and be enriched in glioma; in the acidic environment of tumor tissue, the boronate bond breaks, the negatively charged shell disintegrates, and the positively charged core is exposed, so that it can be better taken up by tumor tissue; under the high concentration of GSH in tumor cells, GSH competes for the coordination sites between Cu, CA and Cur, accelerates the disintegration of the positively charged core, and makes Cur and Cu 2+ Rapid release; on the one hand, the released natural compound Cur directly exerts anti-tumor efficacy; on the other hand, the copper ion-mediated Fenton-like reaction produces toxic ·OH, which can induce apoptosis of tumor cells. The effect is more significant than other drug delivery systems that use a single method to treat brain gliomas;

[0020] (2) The raw materials used in the core-shell nanoparticles of the present invention are non-toxic, harmless and highly biocompatible. For example, CS is a natural cationic polysaccharide widely used as a drug carrier, γ-PGA is an anionic polypolypeptide composed of D- and L-glutamic acid repeating units, Cu is a redox cofactor of many natural enzymes in the human body, and Lf is an important non-heme iron-binding glycoprotein in milk. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Transmission electron microscopy pattern (scale is 200 nm) and appearance pattern of Lf-PP / CC-Cu-Cur NPs;

[0022] Figure 2 is the hydrated particle size diagram of CC-Cu-Cur NP and Lf-PP / CC-Cu-Cur NPs;

[0023] Figure 3 The graph showing the particle size changes of PP / CC-Cu-CurNPs and Lf-PP / CC-Cu-CurNPs after incubation with plasma for 24 h;

[0024] Figure 4 In vitro drug release profiles of free Cur and Lf-PP / CC-Cu-CurNPs at different pH and GSH concentrations;

[0025] Figure 5 Images of ROS production in GL261 cells taken with an inverted fluorescence microscope after incubation with DMEM, CC-Cu-Cur NPs, PP / CC-Cu-CurNPs, and Lf-PP / CC-Cu-Cur NPs for 1 h, 6 h, or 24 h, respectively;

[0026] Figure 6 Images of GL261 cells taken with an inverted fluorescence microscope showing the uptake of free Cur, CC-Cu-Cur NPs, PP / CC-Cu-Cur NPs, and Lf-PP / CC-Cu-Cur NPs at 5 μg / mL, 15 μg / mL, and 20 μg / mL (in terms of Cur) after incubation for 4 h;

[0027] Figure 7 The cell viability was determined by MTT method. DETAILED DESCRIPTION

[0028] In order to better understand the present invention, the present invention is further described below through examples, but the content of the present invention is not limited to the following examples.

[0029] Example 1

[0030] Synthesis of CC

[0031] (1) Weigh 100 mg of CS, dissolve it in 10 mL of acetic acid (1%, v / v), and dilute it with an appropriate amount of methanol while stirring at room temperature;

[0032] (2) 51 mg of CA was weighed and dissolved in an appropriate amount of methanol, and then added to the CS solution. Then, 81.2 mg of EDC and 48.8 mg of NHS were added to react with the amino groups in CS to form an amide bond. The resulting reaction mixture was stirred at room temperature for 24 h.

[0033] (3) The reaction solution was placed in a treated dialysis bag (molecular weight cutoff 3.5 kDa), dialyzed with an excess of water / methanol mixture (1:4, v / v) for 2 days, filtered through a 0.8 μm microporous filter membrane, and then freeze-dried to obtain a light brown CC powder for use.

[0034] Example 2

[0035] Synthesis of PP

[0036] (1) Weigh 17.64 mg of γ-PGA and dissolve it in an appropriate amount of DMSO:H2O (1:1, v / v). After dissolution, add co-catalyst EDC (46 mg) and NHS (27.6 mg) and activate in an ice bath for 1 h.

[0037] (2) slowly adding a small amount of triethylamine dropwise while stirring until the final pH of the solution is adjusted to be weakly alkaline;

[0038] (3) Weigh 22.3 mg PBA and dissolve it in an appropriate amount of DMSO:H2O (1:1, v / v). After it is completely dissolved, add it dropwise into the above γ-PGA solution and react at room temperature for 24 h.

[0039] (4) The reaction solution was placed in a treated dialysis bag (molecular weight cut-off 3.5 kDa), dialyzed in excess pure water for 2 days, filtered through a 0.8 μm microporous filter membrane, and then freeze-dried to obtain a white sponge-like PP solid for use.

[0040] Example 3

[0041] Preparation of CC-Cu-Cur NPs

[0042] (1) Under magnetic stirring, 8.5 mL CC (pH 6.5, 1 mg / mL), 0.5 mL CuCl2 (10 mM), and 1 mL Cur (2 mg / mL) were mixed and reacted at room temperature for 15 min;

[0043] (2) The reaction solution was subjected to rotary evaporation at 40°C to remove ethanol and filtered through a 0.8 μm microporous filter to obtain CC-Cu-Cur NPs.

[0044] Example 4

[0045] Preparation of PP / CC-Cu-Cur NPs

[0046] Under magnetic stirring, 1 mL of CC-Cu-Cur NPs was dropped into 3 mL of 10 mg / mL PP deionized water solution and stirred for 3 h at room temperature to obtain PP / CC-Cu-Cur NPs.

[0047] Example 5

[0048] Preparation of Lf-PP / CC-Cu-Cur NPs

[0049] Under magnetic stirring, 1 ml of Lf with a concentration of 3 mg / mL was dropped into 5 mL of PP / CC-Cu-Cur NPs system and reacted at room temperature for 12 h to obtain Lf-PP / CC-Cu-Cur NPs.

[0050] Example 6

[0051] Nanoparticle transmission electron microscopy and appearance characterization

[0052] See also Figure 1 , drop 0.5 mg / mL of Lf-PP / CC-Cu-Cur NPs sample aqueous solution on the copper grid, wait for the sample to dry completely, and use it for transmission electron microscopy characterization. 0.5 mg / mL of Lf-PP / CC-Cu-Cur NPs sample aqueous solution was placed in a sample bottle for camera to capture the appearance. Figure 1The transmission electron microscope photo and appearance picture of Lf-PP / CC-Cu-CurNPs show that the nanoparticles are spherical in appearance and have a particle size of about 200nm. Cur is an orange-yellow crystalline powder, so the appearance of the preparation is orange-yellow.

[0053] Example 7

[0054] Nanoparticle hydration particle size characterization

[0055] See also Figure 2 After the 0.5 mg / mL CC-Cu-Cur NPs and Lf-PP / CC-Cu-Cur NPs sample aqueous solution was diluted to a certain extent, the hydrated particle size and distribution of the sample were measured using a Malvern laser particle size analyzer. Figure 2 It can be seen that the preparation is evenly dispersed in the aqueous solution, and the hydrated particle sizes of CC-Cu-Cur NPs and Lf-PP / CC-Cu-Cur NPs are about 190nm and 230nm, respectively.

[0056] Example 8

[0057] Plasma stability of nanoparticles

[0058] See also Figure 3 PP / CC-Cu-Cur NPs and Lf-PP / CC-Cu-Cur NPs were mixed with equal volumes of rat plasma (filtered at 0.22 μm), incubated in a water bath at 37°C, and appropriate samples were taken at fixed points to immediately measure the particle size and polydispersity coefficient to investigate the stability of each preparation in plasma. The results showed that the particle size of the two preparations increased slightly by 30-60 nm within the first 0.25-0.5 h of incubation with rat plasma. This may be due to plasma protein adsorption. Since this protein adsorption process is reversible, the particle size change of the nanoparticles subsequently tends to be stable, and no aggregation occurs.

[0059] Example 9

[0060] pH and redox responsive drug release studies

[0061] See also Figure 4, 2mL of Cur solution containing 0.2mg, Lf-PP / CC-Cu-CurNPs were added to a dialysis bag (molecular weight 3.5kDa). The dialysis bag was placed in 50mL of PBS release medium (pH7.4, 6.5, 5.0±10mM GSH) containing 1.0% (v / v) Tween 80, and released at 37°C and 400rpm. The time was set at 0.083, 0.5, 1, 2, 4, 6, 8, 12, 24, 36h, and 0.5mL was sampled outside the dialysis bag, and the same volume of fresh release medium was added. All samples were protected from light during the test, and the release of Cur in the solution was measured at 425nm using a UV-visible spectrophotometer. The experiment was repeated three times, and the data are expressed as mean ± standard deviation.

[0062] The results showed that under the condition of pH 7.4, the 8h cumulative release of Cur solution was above 90%, indicating that the release was complete and the release conditions were appropriate. Under the condition of pH 7.4, the 24h cumulative release of Lf-PP / CC-Cu-CurNPs was about 30%. And as the pH value in the release medium decreased, the cumulative release gradually increased. Under the conditions of pH 6.5 and pH 5.0, the 24h cumulative release was about 35%. This is because as the pH value decreases, the pH-sensitive boronate bond between the core and shell breaks, resulting in the removal of the shell and the exposure of CC-Cu-CurNPs. In order to simulate the tumor microenvironment, we added 10mM GSH to the release medium at pH 5.0. Compared with the pH 5.0 group, the release rate and cumulative release of Lf-PP / CC-Cu-Cur NPs in the pH 5.0+10mM GSH system increased significantly, with a cumulative release of about 50% in 8 hours and more than 60% in 24 hours. This is because GSH competes for the coordination sites between Cu, CA and Cur, accelerates the disintegration of CC-Cu-CurNPs, and promotes the release of Cur. The above experiments confirm that Lf-PP / CC-Cu-Cur NPs have pH and GSH dual-responsive drug release characteristics in the tumor microenvironment.

[0063] Example 10

[0064] Characterization of intracellular ROS production by inverted fluorescence microscopy

[0065] See also Figure 5 GL261 cells in the logarithmic growth phase were taken at a density of 1×10 5 Each well was inoculated in a 24-well plate and cultured in a standard cell incubator for 24 hours before discarding the culture medium. 2+The concentrations of CC-Cu-CurNPs, PP / CC-Cu-Cur NPs, and Lf-PP / CC-Cu-Cur NPs were treated for 1h, 6h, 6h+N-acetylcysteine ​​(NAC, 5mmoL NAC pretreatment for 1h and then added with the preparation), and 24h, respectively, and three parallel control groups were set up in each group. Then the culture medium was removed and washed with PBS three times, and 200μL of DCFH-DA (5μM) detection solution was added to each well and returned to the standard incubator for incubation in the dark for 30min. Each well was washed three times with PBS to fully remove the DCFH-DA detection solution, and the fluorescence was observed under an inverted fluorescence microscope.

[0066] The results showed that at 50 μg / mL Cu 2+ ROS were induced at 1h and 6h after treatment with the preparations of the same concentration, and the green fluorescence of reactive oxygen species generated at 6h was the strongest. Compared with CC-Cu-Cur NPs, the intracellular ROS levels of PP / CC-Cu-Cur NPs and Lf-PP / CC-Cu-CurNPs at 24h were relatively higher, which may be due to the fact that in the tumor microenvironment, PP / CC-Cu-CurNPs and Lf-PP / CC-Cu-CurNPs experienced pH and GSH-responsive drug release, and the sustained release effect was more obvious than that of CC-Cu-CurNPs, and ROS could be continuously generated for a longer time. After pretreatment with the antioxidant NAC, the green fluorescence of reactive oxygen species generated at 6h decreased significantly, indicating that the preparations can cause a significant increase in the intracellular ROS content, and NAC weakened this effect.

[0067] Embodiment 11

[0068] Characterization of cellular uptake of different agents by inverted fluorescence microscopy

[0069] See also Figure 6 Inverted fluorescence microscopy was used to qualitatively study the uptake changes of GL261 cells to different concentrations of Cur solution, CC-Cu-Cur NPs, PP / CC-Cu-Cur NPs, and Lf-PP / CC-Cu-Cur NPs. GL261 cells in the logarithmic growth phase were taken at a density of 1×10 5 Each well was inoculated in a 24-well plate, and after culturing in a standard cell incubator for 24 hours, the culture medium was discarded, and 500 μL / well of Cur solution (Cur concentration was 5, 15, 20 μg / mL), CC-Cu-Cur NPs, PP / CC-Cu-Cur NPs, and Lf-PP / CC-Cu-Cur NPs (diluted with DMEM without FBS) were added to each well and incubated for 4 hours. Then, the culture medium was discarded, the cells were washed three times with PBS, and the uptake of each group of preparations was observed under an inverted fluorescence microscope.

[0070] The results showed that the uptake of Cur solution, CC-Cu-Cur NPs, PP / CC-Cu-Cur NPs and Lf-PP / CC-Cu-Cur NPs by GL261 cells was concentration-dependent, and the fluorescence intensity of the Cur solution group was always weaker than that of the preparation group, indicating that the preparation group had a better promoting effect on the absorption of Cur. This may be because the Cur-loaded nanoparticles are smaller in size and are more easily absorbed by cells through endocytosis, while the highly hydrophobic Cur tends to form larger aggregates and is more difficult to be internalized by cells. Among them, the CC-Cu-CurNPs group showed the most significant green fluorescence accumulation, which may be due to the enhanced affinity between the positively charged nanoformulation and the negative GL261 cell membrane. PP / CC-Cu-Cur NPs and Lf-PP / CC-Cu-Cur NPs need to expose the positively charged core by hydrolyzing the amide bond between the core and shell under the extracellular pH conditions of tumor cells, thereby promoting cell uptake. Compared with PP / CC-Cu-CurNPs, at the same drug concentration, the Lf-PP / CC-Cu-CurNPs group showed stronger green fluorescence accumulation, indicating that the surface modification of Lf promoted the uptake of GL261 cells.

[0071] Example 12

[0072] Nanoparticle cytotoxicity assay

[0073] See also Figure 7 GL261 cells in the logarithmic growth phase were taken and 1×10 4 Each well was inoculated in a 96-well plate and placed in a standard incubator (5% CO2, 37°C) for 24 hours. The culture medium was discarded, and 200 μL / well of Cur solution, CC-Cu-Cur NPs, PP / CC-Cu-Cur NPs and Lf-PP / CC-Cu-Cur NPs (diluted with DMEM medium without FBS) of different concentrations (Cur concentrations were 2.5, 5, 10, 20, 40 μg / mL) were added to each well. After the cells were cultured in a standard incubator for 24 hours, the culture medium was discarded and washed 2-3 times with PBS buffer. 50 μL of MTT solution (0.5 mg / mL, dissolved in pH 7.4 PBS) was added to each well and returned to the incubator for 4 hours. After 4 hours, the supernatant was discarded, 100 μL of DMSO was added to each well, and the crystals were slightly shaken to dissolve, and the absorbance value of each well was measured using an enzyme marker. The cells were incubated in the same manner with blank culture medium as a blank control (100% survival rate). Six replicate wells were made for each sample. The half-maximal inhibitory concentration IC of each drug-loaded preparation on GL261 cells was fitted by cell survival rate-concentration curve. 50 .

[0074] The results showed that the cytotoxic effects of each drug-loaded preparation on GL261 cells were concentration-dependent. With the increase of Cur concentration, the survival rate of GL261 cells decreased. At the same Cur concentration, the cytotoxicity of Cur solution was the lowest, while the cytotoxicity was significantly increased after Cur was loaded into nanoparticles, which was due to the increased cell uptake. Comparing the three preparation groups, when the Cur concentration was below 20μg / mL, CC-Cu-Cur NPs had the highest cytotoxicity, followed by Lf-PP / CC-Cu-Cur NPs, and PP / CC-Cu-Cur NPs had the lowest cytotoxicity. It may be that when the Cur concentration was low, the toxic effect of the positively charged nanoparticles on cells was significantly enhanced. When the Cur concentration was increased to 40μg / mL, the cytotoxicity of Lf-PP / CC-Cu-Cur NPs was equivalent to that of CC-Cu-Cur NPs, which may be due to the significant increase in the amount of Lf-PP / CC-Cu-Cur NPs entering cells through Lf receptor-mediated endocytosis and charge flipping. IC of Cur solution, PP / CC-Cu-Curr NPs, Lf-PP / CC-Cu-Cur NPs and CC-Cu-Cur NPs 50 The values ​​were 26.02μg / mL, 21.76μg / mL, 19.14μg / mL and 15.78μg / mL respectively. The above experimental results show that after PP coating and Lf modification, the cytotoxicity of Lf-PP / CC-Cu-Cur NPs group is higher than that of free Cur group and PP / CC-Cu-Cur NPs group. At the same time, compared with CC-Cu-CurNPs, it has milder cytotoxicity.

Claims

1. A glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticle, characterized in that: The γ-polyglutamic acid / chitosan core-shell nanoparticles are composed of cationic nanoparticles formed by self-assembly driven by caffeic acid (CA) grafted chitosan (CS)-copper-curcumin (Cur) coordination as the core, phenylboronic acid (PBA) modified γ-polyglutamic acid (γ-PGA) as the anionic shell, and are combined with each other through electrostatic action and pH-sensitive borate bonds to form γ-polyglutamic acid / chitosan core-shell nanoparticles; then, lactoferrin (Lf) is further modified on the surface of the nanoparticles through electrostatic adsorption to construct a glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticle.

2. The glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticles according to claim 1, characterized in that: The γ-polyglutamic acid / chitosan core-shell nanoparticles are based on CS grafted with CA as the skeleton (CC), the amino group in CS and the catechol structure in CA are selected as the high-affinity anchor points for the coordination of the nanoparticles, divalent copper (Cu(II)) is used as the coordination bridge and intermediate, and Cur has a diketone / enol part with coordination binding ability, and a glutathione (GSH) responsive drug delivery system (CC-Cu-Cur NPs) based on coordination-driven self-assembly is prepared; PBA-grafted γ-PGA (PP) is selected as the shell to shield the positive charge of CC-Cu-Cur NPs, and the positively charged core CC-Cu-Cur NPs and the negatively charged shell PP are combined with each other through electrostatic interaction and pH-sensitive boronate bonds to form γ-polyglutamic acid / chitosan core-shell nanoparticles (PP / CC-Cu-CurNPs); finally, electrostatic interaction is used to adsorb positively charged Lf on the surface of the nanoparticles to construct a glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticle (Lf-PP / CC-Cu-Cur NPs), which can penetrate the blood-brain barrier (BBB) ​​to further target gliomas and have pH / redox dual response capabilities; after Lf-PP / CC-Cu-Cur NPs enter the blood circulation through intravenous injection, they are enriched in the brain region through the BBB due to the targeting effect of Lf; PBA can further bind to the sialic acid (SA) receptors overexpressed on the surface of tumor cells, and Lf can also bind to the low-density lipoprotein receptor-related protein 1 (LRP-1) on the surface of tumor cells, so that Lf-PP / CC-Cu-Cur NPs are enriched in gliomas; The pH-responsive borate bond breaks upon reaching the tumor microenvironment (pH 6.5), and the anionic shell PP is removed, exposing the positively charged core CC-Cu-CurNPs, which is easier to be taken up by tumor cells: the high concentration of GSH in tumor cells competes for the coordination sites between Cu, CA and Cur, accelerating the disintegration of the positively charged core, causing Cur and Cu to react with each other. 2+ Rapid release; on the one hand, the released natural compound Cur directly exerts anti-tumor efficacy; on the other hand, the copper ion-mediated Fenton-like reaction produces toxic ·OH, which can induce apoptosis of tumor cells.

3. The method for preparing a glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticle according to claim 1, characterized in that: The method comprises the following specific steps: (1) Weigh 100 mg of CS, dissolve it in 10 mL of acetic acid (1%, v / v), and dilute it with an appropriate amount of methanol while stirring at room temperature; dissolve 51 mg of CA in an appropriate amount of methanol and add it to the CS solution; then continue to add catalyst EDC (81.2 mg) and NHS (48.8 mg) to react with the amino group in CS to form an amide bond; the resulting reaction mixture is stirred at room temperature for 24 h, dialyzed with an excess of water / methanol mixture (1:4, v / v) for 2 days, filtered through a 0.8 μm microporous filter membrane, and then freeze-dried to obtain a light brown CC powder for use; (2) Weigh 17.64 mg of γ-PGA and dissolve it in an appropriate amount of DMSO:H2O (1:1, v / v). After dissolution, add catalyst EDC (46 mg) and NHS (27.6 mg) and activate in an ice bath for 1 h. Then slowly add a small amount of triethylamine dropwise while stirring until the pH of the final solution is adjusted to be weakly alkaline. Weigh 22.3 mg of PBA and dissolve it in an appropriate amount of DMSO:H2O (1:1, v / v). After complete dissolution, add it dropwise to the above γ-PGA solution, react at room temperature for 24 h, dialyze in pure water for 2 days, filter through a 0.8 μm microporous filter membrane, and then freeze-dry to obtain a white sponge-like PP solid for use. (3) Under magnetic stirring, 8.5 mL CC (pH 6.5, 1 mg / mL), 0.5 mL CuCl2 (10 mM), and 1 mL Cur (2 mg / mL) were mixed and reacted at room temperature for 15 min. Subsequently, the reaction solution was rotary evaporated at 40 °C to remove ethanol and filtered through a 0.8 μm microporous filter to obtain CC-Cu-Cur NPs. (4) Under magnetic stirring, 1 mL of CC-Cu-Cur NPs was dropped into 3 mL of 10 mg / mL PP deionized water solution and stirred for 3 h at room temperature to obtain PP / CC-Cu-Cur NPs; (5) Under magnetic stirring, 1 ml of 3 mg / mL Lf was added dropwise to 5 mL of PP / CC-Cu-Cur NPs system and reacted at room temperature for 12 h to obtain Lf-PP / CC-Cu-Cur NPs.

4. Use of the glioma-targeted γ-polyglutamic acid / chitosan core-shell nanoparticles according to claim 1 in the preparation of glioma products.